亚院二年级学生使用汉语时量补语的偏误分析 KESALAHAN PENGGUNAAN FRASE KOMPLEMEN DURASI PADA MAHASISWA STBA-PIA SEMESTER IV - Karina karina; Nico Nico (Journal of Language, Literature and Teaching, 2022)
This study used descriptive qualitative research method to describe and analyze 16 students’ exercise while using Chinese complement of duration phrase. This study also used Miles, Huberman, and Saldana for the data analysis. According to Yang’s theory, Chinese complement of duration phrase has four common formulas, which are S1: S＋V（＋了）＋时量补语（＋了）; S2: S＋V（＋了）＋时量补语（＋的）＋O（＋了）（O为一般名词）; S3: S＋V（＋了）＋O＋V＋时量补语（＋了）; S4: S＋V（＋了）＋O＋时量补语（＋了）（O为人称代词/确定的人的名词. Each student was given 10 Indonesian sentences to translate into Chinese sentences using this phrase. According to the results, there were 37 error of omission sentences (49%), 34 disordering sentences (45%), 2 error of addition sentences (3%) and 2 error of substitution sentences (3%). Through interviewing these students, there was one factor that causes error in those sentences; it was intralingual factor in which students did not really understand to use complement of duration. Key Words: complement of duration phrase; Error analysis; Qualitative research